URDU-RESOLUTION OF AQUATIC ISSUES IN THE LIGHT OF ISLAMIC INSTRUCTIONS : A SPECIAL STUDY IN PAKISTANI PERSPECTIVE - Allah Ditta; Muhammad Amjad (دی اسکالر)
This investigation aims at to present the Islamic view about the protection of water sources, its significance, comparison with modern study and to depict the distinctions and similitudes if any. Furthermore, this study will exhibit that Islamic learning could play a pivotal part in protection of water sources, conserving its usage and avoiding its wastage. But unfortunately, this aspect is neglected in our curricula that is why the people are unaware about its importance, consumption and scarcity. Water sources not only in the world but also in our country are getting to be depleted and contaminated very quickly. Today, around 60 percent of water sources are too polluted and exhausted for swimming and aquaculture. This situation demands some most appropriate and suitable simple measures from the human beings of the entire world otherwise the shortage of the water would not far away from us in some decades and the whole world would become a barren desert. By simply executing a few sustainability initiatives by promulgating and disseminating the Islamic learning, we can save water and avert contamination. In this way, we could save the precious life of our forthcoming generations and protect the aquatic and terrestrial animals and plants too. In this study, creativities and procedures to protect the water sources have been described in the light of Shariah and according to modern research tools of water research and technology.